INDUSTRIAL RELATIONS ENVIRONMENT IN NIGERIA: REVIEWING CONFLICT CAUSES AND TAXANOMIES AMONG PUBLIC SECTOR EMPLOYEES - Sabo, Abubakar; Maishanu, Malami Muhammad; Muhammad, Sani (Indonesian Journal Of Business And Economics, 2018)
The institutional and legal framework of bargaining that has been established in Nigeria can be seen as encapsulating the shape, rather than the substance, of meaningful industrial relations. As such it closely corresponds to the broader disagreement existing in other areas of social life between the constitutional, legal, and normative mores inherited from the colonial government and real behavior patterns. The main issues that divide wage earners, on the one hand, from employers and government, on the other, have an existence far alienated from the recognized system of industrial relations, while the unions, the employers, and the government continue to give formal adherence to the system. As a response to the need to resolve issues between employers and their workers speedily, the Industrial Arbitration Panel [IAP] was established in 1976. The Act which was established vested the Panel with jurisdiction to hear and determine trade disputes between workers and employers, including inter and intra Union disputes in both private and public sectors of Nigeria. The paper seeks to review the industrial relations environment in Nigeria. It emphasizes on how conflict and its taxonomies shapes the behavior of public sector employees. The paper equally concludes that the causes of conflict among public sector employees is greatly influenced by the inter-play of institutional, political and legal factors within the industrial relations environment.